2018
DOI: 10.20964/2018.05.173
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Critical Pitting Temperature (CPT) of Super Duplex Stainless Steel S32707 in NaCl Solution

Abstract: In this study, the critical pitting temperature (CPT) of super duplex stainless steel UNS S32707 was compared using potentiodynamic, potentiostatic techniques, EIS and new electrochemical noise method. The results revealed that the CPT of S32707 is between 55-65 °C for potentiodynamic polarization and 64 °C for potentiostatic polarization, respectively. The pitting corrosion of S32707 occurs at about 65 °C for EIS method and the CPT value is between 58-65 °C for electrochemical noise method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The analysis of research results was performed using the ZSimpWin optimization program. Since no pitting corrosion is initiated during EIS measurement, the Nyquist replacement scheme can be used to optimize results [15,16]. An equivalent circuit generated through frequency fitting from all studied spectra is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of research results was performed using the ZSimpWin optimization program. Since no pitting corrosion is initiated during EIS measurement, the Nyquist replacement scheme can be used to optimize results [15,16]. An equivalent circuit generated through frequency fitting from all studied spectra is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…4, that a unique value cannot be allocated to the CPT of 2205 DSS specimens using potentiodynamic experiments. It has been previously reported that allocating a unique value to CPT by means of PDP experiments is often infeasible, 62,[67][68][69][70][71][72][73] unless in some cases when the measurements are performed at very narrow temperature intervals. [74][75][76] Recently, Sun et al 76 measured breakdown potentials for 316L, 317L, 904L, and 254SMO austenitic SSs at narrow temperature intervals and discovered a quite sharp transition from transpassivity to pitting for these steels, at a temperature that was regarded as CPT.…”
Section: Microstructurementioning
confidence: 99%
“…Despite the very successful applications and experience of DSSs, the development of highly alloyed DSSs has been very active since there are still areas where the corrosion resistance of the current DSSs has been insufficient for a long service life or at higher temperatures. Based on this challenge, the flagship hyper DSS, UNS S33207 (marked as S33207 from herein), which has the highest corrosion resistance and strength among the existing modern DSSs has since been developed [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%